Moral Licensing—Another Source of Rebound? - Dütschke, Elisabeth; Frondel, Manuel; Schleich, Joachim; Vance, Colin (Frontiers in Energy Research, 2018)
The rebound effect denotes an offset in energy savings that occurs when an individual increases consumption of a good or service following an increase in its efficiency. It has both economic and psychological underpinnings: In addition to the price, income and substitution effects emphasized by economists, psychologists point to the influence of moral licensing, the cognitive process by which individuals justify immoral behavior (e.g., driving more) by having previously engaged in moral behavior (e.g., purchasing a more efficient car). The present review article provides a conceptual and empirical overview of moral licensing, drawing comparisons with economic explanations for the rebound effect. Based on a unifying theoretical model that illustrates how economic and psychological motivations trigger both rebound and moral licensing effects, as well as a review of microeconometric and experimental evidence, we conclude that consideration of moral licensing is warranted for judging the efficacy of policies targeted at energy consumption and the rebound effect.